2005
DOI: 10.1021/es040545j
|View full text |Cite
|
Sign up to set email alerts
|

Copper Toxicity to Larval Stages of Three Marine Invertebrates and Copper Complexation Capacity in San Diego Bay, California

Abstract: Temporal and spatial measurements of the toxicity (EC50), chemical speciation, and complexation capacity (Cu-CC) of copper in waters from San Diego Bay suggest control of the Cu-CC over copper bioavailability. While spatial distributions of total copper (CuT) indicate an increase in concentration from the mouth toward the head of San Diego Bay, the distribution of aqueous free copper ion (Cu(II)aq) shows the opposite trend. This suggests that the bioavailability of copper to organisms decreases toward the head… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
31
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 15 publications
5
31
0
Order By: Relevance
“…Ultimately, proof that the copper(II) ISE is indeed a reliable tool for the environmental analysis of free copper(-II) in natural waters was provided in recent papers by Eriksen et al [43] and Rivera-Duarte et al [44] who conducted copper speciation and toxicity studies of a marine diatom and three larval species using the jalpaite copper(II) ISE. In each of these studies, seawater containing nanomolar concentrations of total copper (Macquarie Harbour seawater in Eriksen et als study [43], and San Diego Bay seawater in the study of Rivera-Duarte et al [44]) was spiked with varying levels of copper, and total and free copper levels were assayed by GFAAS and copper(II) ISE potentiometry respectively, while the toxicological responses towards marine species (viz., growth inhibition of the marine diatom [43] and LC 50 values for larval development of three marine invertebrates [44]) were recorded simultaneously.…”
Section: Free Copper and Toxicology Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultimately, proof that the copper(II) ISE is indeed a reliable tool for the environmental analysis of free copper(-II) in natural waters was provided in recent papers by Eriksen et al [43] and Rivera-Duarte et al [44] who conducted copper speciation and toxicity studies of a marine diatom and three larval species using the jalpaite copper(II) ISE. In each of these studies, seawater containing nanomolar concentrations of total copper (Macquarie Harbour seawater in Eriksen et als study [43], and San Diego Bay seawater in the study of Rivera-Duarte et al [44]) was spiked with varying levels of copper, and total and free copper levels were assayed by GFAAS and copper(II) ISE potentiometry respectively, while the toxicological responses towards marine species (viz., growth inhibition of the marine diatom [43] and LC 50 values for larval development of three marine invertebrates [44]) were recorded simultaneously.…”
Section: Free Copper and Toxicology Studiesmentioning
confidence: 99%
“…In each of these studies, seawater containing nanomolar concentrations of total copper (Macquarie Harbour seawater in Eriksen et als study [43], and San Diego Bay seawater in the study of Rivera-Duarte et al [44]) was spiked with varying levels of copper, and total and free copper levels were assayed by GFAAS and copper(II) ISE potentiometry respectively, while the toxicological responses towards marine species (viz., growth inhibition of the marine diatom [43] and LC 50 values for larval development of three marine invertebrates [44]) were recorded simultaneously. In both studies, there was a clear correlation between the toxicological response of marine species to copper in seawater, and the free copper(II) levels determined using the ISE, not total copper levels assayed using GFAAS.…”
Section: Free Copper and Toxicology Studiesmentioning
confidence: 99%
“…These results show that cyanobacteria and many plankton species are likely to be highly compromised in the Creek, as studies showed that their viability declined at concentrations in the range 0.001-0.1 nM Cu 2+ (Brand et al, 1986;Sunda et al, 1987). Furthermore, larvae bioassays of higher organisms, such as sea urchin (Strongylocentrotus purpuratus), mussel (Mytilus galloprovincialis) and oyster (Crassostrea gigas), exhibited sensitivity toward Cu 2+ at EC 50 6 0.90 nM, EC 50 6 0.06 nM and EC 50 = 0.23 ± 0.08 nM, respectively (Rivera-Duarte et al, 2005;Money, 2008), and hence the development of juveniles of such organisms is likely to be severely impaired at the study location. The calculated minimal and maximal concentrations of Cd 2+ and Pb 2+ were in the sub-nanomolar range for both surveys (0.009-0.18 nM Cd 2+ and 0.008-0.028 nM Pb 2+ ).…”
Section: Impacts On Biotamentioning
confidence: 99%
“…Various techniques have been applied to the speciation of copper in environmental matrices, such as surface waters and soil solutions. The most often used are pH potentiometry, [6] cation-exchange resins, [7][8][9] charge separation (Donnan membrane), [10,11] anodic stripping voltammetry, [7,[12][13][14][15][16][17][18][19] diffusive gradients in thin films measurements [18] and cupric ion-selective electrodes (ISE). [3,14,15,[18][19][20][21][22][23][24][25] All these techniques have some advantages and disadvantages and none can be considered universal.…”
Section: Introductionmentioning
confidence: 99%